Ultralow-density high-strength ceramsite proppant and preparation method thereof

By using gangue, kaolin, talc, dolomite, and starch cellulose as raw materials, and combining jaw crushing, ball milling, and pressureless calcination processes, an ultra-low density, high-strength ceramsite proppant that meets industry standards has been prepared. This has solved the problems of high cost, low strength, poor sphericity, and high acid solubility in existing technologies, and has achieved good application results.

CN119823746APending Publication Date: 2025-04-15ZHENGZHOU XINYUAN WEAR RESISTANT MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510089600.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing ultra-low density ceramic proppant suffers from high preparation costs, low strength, poor sphericity, and high acid solubility, making it difficult to meet the needs of shale gas and coalbed methane extraction.

Method used

Ultra-low density, high-strength ceramic proppant was prepared using gangue, kaolin, talc, dolomite, and starch cellulose as main raw materials through jaw crushing, ball milling, granulation, and pressureless calcination processes, with the calcination temperature controlled between 1200℃ and 1400℃.

Benefits of technology

An ultra-low density, high-strength ceramic proppant conforming to the SY/T5108-2014 industry standard was prepared, exhibiting good roundness, sphericity, and low acid solubility, thus meeting the requirements for ultra-low density applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of oil and gas exploitation, and discloses an ultralow-density high-strength ceramsite proppant and a preparation method thereof.The ultralow-density high-strength ceramsite proppant is prepared from, by mass, 65%-75% of gangue, 10%-20% of kaolin, 3%-10% of talc, 3%-8% of dolomite and 0.5%-1.5% of starch cellulose; the ceramsite proppant is formed by carrying out pressureless calcination at the temperature of 1200 DEG C to 1400 DEG C. The ultra-low-density and high-strength ceramsite proppant prepared by taking the gangue and the kaolin as main raw materials meets the SY / T5108-2014 industrial standard requirements, also meets the application requirements of ultra-low density and high strength, and also has good roundness and sphericity and relatively low acid solubility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the field of oil and gas exploitation, and in particular to an ultra-low density and high-strength ceramsite proppant and a preparation method thereof. Background Art

[0004] With the development of society and the pressure of the environment, the proportion of clean energy in my country's energy structure will gradually increase, and conventional natural gas resources, as well as unconventional natural gas resources such as coalbed methane and shale gas will become important energy sources in the future. Due to the particularity of geological structure and the requirements of environmental protection, ultra-low density and high-strength ceramsite proppants have become key materials that are urgently needed to be developed in the exploitation of unconventional natural gas resources such as shale gas and coalbed methane.

[0005] In the prior art, the ceramsite proppant prepared with gangue and kaolin as the main raw materials is a low-density ceramsite proppant with a bulk density of 1.4 g / cm 3 ~1.65 g / cm 3 , and the bulk density is less than 1.3 g / cm 3 Only the ceramsite proppant with good density can be called ultra-low density ceramsite proppant. The current ultra-low density ceramsite proppant is mainly prepared from bauxite, which not only cannot meet the application requirements of ultra-low density proppant, but also has defects such as high preparation cost, low strength, poor sphericity, and high acid solubility.

[0006] Based on this, the present invention provides an ultra-low density and high-strength ceramsite proppant with low preparation cost, good sphericity and low acid solubility to meet the use requirements. Summary of the invention

[0008] The present invention aims to solve the technical problems existing in the prior art. To this end, the present invention provides an ultra-low density and high-strength ceramsite proppant with low preparation cost, good sphericity and low acid solubility.

[0009] The technical solution adopted by the present invention to solve its technical problem is: Provided is an ultra-low density and high-strength ceramsite proppant, which is made of the following raw materials in percentage by mass: 65%-75% of gangue, 10%-20% of kaolin, 3%-10% of talc, 3%-8% of dolomite, and 0.5%-1.5% of starch cellulose; the ceramsite proppant is formed by pressureless calcination at a temperature of 1200°C-1400°C.

[0010] Preferably, the proppant is made of the following raw materials in percentage by mass: 68% to 74% gangue, 10% to 20% kaolin, 5% to 10% talc, 3% to 8% dolomite, and 0.8% to 1.3% starch cellulose; the ceramsite proppant is pressurelessly calcined at a temperature of 1200° C. to 1250° C.

[0011] The ceramsite proppant is prepared as follows: Step S1, crushing: crushing the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm using a jaw crusher; Step S2, ball milling: putting gangue, kaolin, talc, dolomite, and starch cellulose in a set mass percentage into a ball mill for ball milling, and selecting fine powder with a mesh size of >500 through a powder selector after ball milling; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The ultra-low density and high strength ceramsite proppant prepared by using gangue and kaolin as main raw materials meets the requirements of SY / T5108-2014 industry standard, also meets the application needs of ultra-low density and high strength, and also has good roundness, sphericity and low acid solubility. DETAILED DESCRIPTION

[0014] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0015] The embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Embodiment 1 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 65%~75%, kaolin 10%~20%, talc 3%~10%, dolomite 3%~8%, starch cellulose 0.5%~1.5%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1300° C. to 1350° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0017] The volume density of the prepared ceramsite proppant is 1.28 g / cm 3 The crushing rate is 3.32% under the closing pressure of 52MPa, the acid solubility is 3.07%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0018] Embodiment 2 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 67%~75%, kaolin 10%~15%, talc 5%~10%, dolomite 3%~6%, starch cellulose 1.0%~1.5%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1260° C. to 1310° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0019] The volume density of the prepared ceramsite proppant is 1.25 g / cm 3 The crushing rate is 3.13% under the closing pressure of 52MPa, the acid solubility is 2.87%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0020] Embodiment 3 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 66%~71%, kaolin 12%~17%, talc 5%~9%, dolomite 5%~8%, starch cellulose 1.0%~1.5%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1260° C. to 1310° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0021] The volume density of the prepared ceramsite proppant is 1.25 g / cm 3 The crushing rate is 3.19% under the closing pressure of 52MPa, the acid solubility is 2.85%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0022] Embodiment 4 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 68%~74%, kaolin 10%~20%, talc 5%~10%, dolomite 3%~8%, starch cellulose 0.8%~1.3%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1200° C. to 1250° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0023] The volume density of the prepared ceramsite proppant is 1.22 g / cm 3 The crushing rate is 2.98% under the closing pressure of 52MPa, the acid solubility is 2.22%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0024] Embodiment 5 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 65%~70%, kaolin 12%~20%, talc 4%~9%, dolomite 4%~7%, starch cellulose 0.8%~1.3%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1220° C. to 1270° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0025] The volume density of the prepared ceramsite proppant is 1.22 g / cm 3 The crushing rate is 3.05% under the closing pressure of 52MPa, the acid solubility is 2.71%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0026] Embodiment 6 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 67%~75%, kaolin 12%~18%, talc 3%~8%, dolomite 3%~7%, starch cellulose 1.0%~1.5%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1300° C. to 1350° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0027] The volume density of the prepared ceramsite proppant is 1.26 g / cm 3 The crushing rate is 3.26% under the closing pressure of 52MPa, the acid solubility is 2.95%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0028] Embodiment 7 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 66%~72%, kaolin 15%~20%, talc 5%~10%, dolomite 3%~8%, starch cellulose 0.5%~1.0%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1270° C. to 1320° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0029] The volume density of the prepared ceramsite proppant is 1.25 g / cm 3 The crushing rate is 3.06% under the closing pressure of 52MPa, the acid solubility is 2.88%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0030] Embodiment 8 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 65%~75%, kaolin 15%~19%, talc 4%~8%, dolomite 5%~8%, starch cellulose 0.5%~1.0%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1260° C. to 1310° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0031] The volume density of the prepared ceramsite proppant is 1.24 g / cm 3 The crushing rate is 3.06% under the closing pressure of 52MPa, the acid solubility is 2.86%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0032] Embodiment 9 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 67%~72%, kaolin 15%~20%, talc 4%~8%, dolomite 3%~5%, starch cellulose 0.5%~1.0%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1270° C. to 1320° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0033] The volume density of the prepared ceramsite proppant is 1.25 g / cm 3 The crushing rate is 3.20% under the closing pressure of 52MPa, the acid solubility is 2.87%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0034] Embodiment 10 S1. Use jaw crusher to crush the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm; Step S2, ball milling: put the following raw materials in terms of mass percentage into a ball mill for ball milling: Gangue 69%~75%, kaolin 10%~14%, talc 3%~7%, dolomite 5%~8%, starch cellulose 0.5%~0.9%; After ball milling, the powder is selected by a powder selector to obtain fine powder with a mesh size of >500; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, the calcination temperature is controlled at 1330° C. to 1380° C., and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.

[0035] The volume density of the prepared ceramsite proppant is 1.29 g / cm 3 The crushing rate is 3.59% under the closing pressure of 52MPa, the acid solubility is 3.22%, the roundness is ≥0.9, and the sphericity is ≥0.9.

[0036] According to the above embodiments, the optimal raw material composition of the ultra-low density and high-strength ceramsite proppant is as follows: 68% to 74% gangue, 10% to 20% kaolin, 5% to 10% talc, 3% to 8% dolomite, and 0.8% to 1.3% starch cellulose, which is formed by pressureless calcination at a temperature of 1200° C. to 1250° C.

[0037] Among the above raw materials, kaolin has good physical and chemical properties such as plasticity and fire resistance. At high temperature, kaolin decomposes to form mullite, forming the main framework of the green body strength, bearing load without invariance, making the firing temperature wider, and making up for the shortcomings of gangue performance. Appropriate amount of kaolin used in the production of ceramsite proppants can increase the strength of the product and improve the roundness and sphericity of the product.

[0038] Talc is a silicate mineral with lubricity, fire resistance, acid resistance and other properties. It can increase the stability of the product shape, increase the pressure strength of the product, and reduce deformation and elongation. After calcination, the product has uniform density, smooth surface, good sphericity, and its biggest characteristic is that it reduces the acid solubility of the product.

[0039] Dolomite can act as a flux and reduce the calcination temperature. An appropriate amount of dolomite helps to form a large amount of corundum phase and a small amount of mullite, thereby improving the strength.

[0040] Starch cellulose can make the ceramsite proppant particles generate liquid phase at a lower temperature, promoting the mutual contact of the reaction components in the particles. The appropriate amount of starch cellulose is conducive to the growth and development of mullite crystals and improves the strength of ceramsite proppant.

[0041] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An ultra-low density and high strength ceramsite proppant, characterized in that: Made of the following raw materials in percentage by mass: Gangue 65%-75%, kaolin 10%-20%, talc 3%-10%, dolomite 3%-8%, starch cellulose 0.5%-1.5%; the ceramsite proppant is formed by pressureless calcination at a temperature of 1200°C-1400°C.

2. The ultra-low density and high strength ceramsite proppant according to claim 1, characterized in that: The ceramsite proppant is made of the following raw materials in percentage by mass: 68% to 74% of gangue, 10% to 20% of kaolin, 5% to 10% of talc, 3% to 8% of dolomite, and 0.8% to 1.3% of starch cellulose; the ceramsite proppant is formed by pressureless calcination at a temperature of 1200° C. to 1250° C.

3. A method for preparing a ceramsite proppant, characterized in that: The ultra-low density and high strength ceramsite proppant according to claim 1 or 2 is prepared by the following steps: Step S1, crushing: crushing the selected gangue, kaolin, talc and dolomite into particles of 1-5 mm using a jaw crusher; Step S2, ball milling: putting gangue, kaolin, talc, dolomite, and starch cellulose in a set mass percentage into a ball mill for ball milling, and selecting fine powder with a mesh size of >500 through a powder selector after ball milling; Step S3, granulation: the selected fine powder is granulated in a granulator by water atomization to obtain spherical semi-finished granules; Step S4, screening: the spherical semi-finished product particles are screened through a drum screen to obtain spherical particles of 300-600 μm; Step S5, calcination: the spherical particles are subjected to pressureless calcination treatment, and after cooling, an ultra-low density and high-strength ceramsite proppant is obtained.